The influence of the Jigsaw learning model on mutual respect attitudes for grade VIII junior high school students - Nadya, Lucky; Santoso, Ridwan (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
This study aims to determine the effect of the use of Jigsaw learning model on mutual respect in grade VIII junior high school students. The study population consisted of 3 classes totaling 72 students. The sample of this research is class VIII students, amounting to 23 students. The determination of the sample class of this study was carried out using random sampling techniques. The research data were obtained through the distribution of pre-test and post-test in which validity were tested using the product moment formula. Research data were analyzed using quantitative techniques through independent sample t-test. The results showed that the use of the Jigsaw learning model had a significant effect on the mutual respect of students in the eighth grade. The results of this study can be a reference for education practitioners and related parties in an effort to instill mutual respect for students in schools, especially in the learning process.These findings can be further research material to find models, methods, or media that can be used by education practitioners and related parties for character education in schools.